2018
DOI: 10.1167/iovs.17-23209
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Antigen Expression in Conjunctival Melanoma Is Not Associated With PD-L1/PD-1 Status

Abstract: Our data indicate that subsets of CM have positive HLA class I expression, and HLA class I and PD-L1/PD-1 are expressed independently. When one considers immunotherapy, one should also analyze HLA class I expression, whose downregulation can limit the efficacy of T cell-mediated therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Although MHC class I loss has been reported in several types of tumors ranging from 15% to 96% 12,13,18,19 , few studies have assessed the proportion of concomitant expression of MHC class I and PD-L1, whereas some have analyzed a single parameter’s expression and relation with immune cell infiltration only 2022 . Our data suggested that the frequency of MHC class I loss with concurrent PD-L1 expression was approximately 7.0% in our tissue microarray cohort, which is similar to 7% in non-small cell lung cancer 23 and 4.3% in conjunctival melanoma 24 . However, the prevalence is higher in esophageal squamous cell carcinoma (12.2%) 25 , non-small cell lung cancer (17%) 26 , and hepatocellular carcinoma (17%) 27 .…”
Section: Discussionsupporting
confidence: 72%
“…Although MHC class I loss has been reported in several types of tumors ranging from 15% to 96% 12,13,18,19 , few studies have assessed the proportion of concomitant expression of MHC class I and PD-L1, whereas some have analyzed a single parameter’s expression and relation with immune cell infiltration only 2022 . Our data suggested that the frequency of MHC class I loss with concurrent PD-L1 expression was approximately 7.0% in our tissue microarray cohort, which is similar to 7% in non-small cell lung cancer 23 and 4.3% in conjunctival melanoma 24 . However, the prevalence is higher in esophageal squamous cell carcinoma (12.2%) 25 , non-small cell lung cancer (17%) 26 , and hepatocellular carcinoma (17%) 27 .…”
Section: Discussionsupporting
confidence: 72%
“…Regarding innate and adaptive immune cells, no clear conclusion can be drawn because of the contradictory results regarding the role of tumour infiltrate lymphocytes (TILs) and tumour-associated macrophages (TAMs) [ 36 , 37 , 38 , 39 , 40 , 41 ]. Elevated levels of HLA Class I are associated with more TILs and TAMs and the expression of PD-L1 in CM seems almost similar to that found in cutaneous melanoma, even if lower percentages of expression levels have been reported [ 41 , 42 , 43 ]. The relevance of this predictive effect may be limited because, as with cutaneous melanoma, CMs with high PD-L1 levels have been shown to respond to PD-1 inhibitors [ 44 ].…”
Section: Biology Of Conjunctival Melanomamentioning
confidence: 63%
“…In some malignancies, both “soft” (reversible) and “hard” (irreversible) downregulation of HLA-I may limit effective T cell immune responses. 51 , 52 Interestingly, reduced HLA-I expression is very common in melanoma prior to immune checkpoint therapy and associated with primary resistance to ipilimumab, but not to nivolumab. 51 In metastatic melanoma patients, regression of metastasis after immunotherapy is associated with the expression of HLA-I APM components and IFN-regulated rejections genes.…”
Section: Discussionmentioning
confidence: 99%